The degradation of lignocellulose in a biologically-generated sulphidic environment - Roman, Henry James (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
South Africa is renowned for its mining industry. The period over which the polluted waters from the existing and abandoned mines will require treatment has driven research into the development of passive treatment systems. These waters are characterised by a low pH, high concentrations of heavy metals, high levels of sulphate salts and low concentrations of organic material. The biological treatment of these waters has been a subject of increasing focus as an alternative to physicochemical treatment. The utilisation of lignocellulose as a carbon source has been restricted by the amount of reducing equivalents available within the lignocellulose matrix. After a few months of near 100% sulphate reduction, it was found that although there was a large fraction of lignin and cellulose remaining, sulphate reduction was reduced to less than 20%. The present study demonstrated that lignocellulose can be utilised as a carbon source for sulphate reduction. It was established that lignocellulose degradation was enhanced under biosulphidogenic conditions and that lignin could be degraded by a sulphate reducing microbial consortium. It was established using lignin model compounds synthesized in our laboratory, that the bonds within the lignin polymer can be cleaved within the sulphidic environment. The presence of cellulolytic enzymes, using CMCase as a marker enzyme, was detected within the sulphate reducing microbial consortium. Based on the results obtained a descriptive model was formulated for the degradation of lignocellulose under biosulphidogenic conditions. It was determined that the initial reduction in sulphate observed using lignocellulose as a carbon source was due to the easily extractable components. The degradation of which resulted in the production of sulphide, which aided in the degradation of lignin, allowing greater access to cellulose. Once the easily extractable material is exhausted, the cycle is halted, unless the sulphide production can be maintained. This is the focus of an ongoing project, testing the hypothesis that an easy to assimilate carbon source added after exhaustion of the easily extractable material, can maintain the sulphide production.
Keywords: Lignocellulose; Sulfides; Lignin; Lignocellulose -- Biodegradation; Mines and mineral resources -- Waste disposal; Acid mine drainage